Sleep quality and associated factors among people who inject drugs in Iran: a nationwide survey using respondent-driven sampling - Rahmatollah Moradzadeh; Khosro Sadeghniiat-Haghighi; Arezu Najafi; Hamid Sharifi; Narges Abdolmohamadi; Fatemeh Hadavandsiri; Samaneh Akbarpour (BMC, 2024)
Abstract Background Poor sleep quality is a significant issue among people who inject drugs (PWID). This study aimed to evaluate sleep quality and associated factors among PWID in Iran. Methods Using respondent-driven sampling, 2,652 PWID (2,563 male) were recruited in 11 major cities in Iran between 2019 and 2020. The Pittsburgh Sleep Quality Index was utilized to measure sleep quality, and logistic regression was used to assess associations in RDSAnalyst, a software designed for respondent-driven sampling. Results The overall prevalence of poor sleep quality was 68.4% (68.3% among males and 70.2% among females). Married PWID had higher odds of poor sleep quality (Adjusted Odds Ratio (AOR): 1.41; 95% CI: 1.05, 1.91). Lack of access to sufficient food in the past 12 months was also associated with poor sleep quality (AOR: 1.73; 95% CI: 1.17, 2.57 for sometimes having no access, and AOR: 2.95; 95% CI: 1.93, 4.52 for always having no access compared to always having access). Additionally, good self-rated health was significantly associated with lower odds of poor sleep quality (AOR: 0.19; 95% CI: 0.11, 0.31). Conclusion Poor sleep quality is prevalent among PWID in Iran. It is recommended to mitigate the adverse effects of this issue and enhance the overall quality of life for PWID. Supportive interventions aimed at preventing and treating poor sleep quality, as well as improving overall health outcomes, are essential.